2022
DOI: 10.1096/fj.202200841r
|View full text |Cite
|
Sign up to set email alerts
|

Lipids uniquely alter secondary structure and toxicity of lysozyme aggregates

Abstract: time when the intensity of ThT fluorescence reached 50% of the maximum; tgrow, time when the intensity of ThT fluorescence reached 90% of the maximum; ThT, thioflavin T; tlag, time when the intensity of ThT fluorescence reached 10% of the maximum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
67
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(81 citation statements)
references
References 54 publications
12
67
0
Order By: Relevance
“…34 In this case, endosomal damage is followed by enhanced ROS levels and mitochondrial damage that ultimately led to cell death. 34,54 Matveyenka and co-workers also found that amyloid aggregates caused significant damage of cell endoplasmic reticulum via the activation of unfolded protein response. 62 These results demonstrate that amyloid-induced cell death can involve multiple molecular mechanisms.…”
Section: ■ Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…34 In this case, endosomal damage is followed by enhanced ROS levels and mitochondrial damage that ultimately led to cell death. 34,54 Matveyenka and co-workers also found that amyloid aggregates caused significant damage of cell endoplasmic reticulum via the activation of unfolded protein response. 62 These results demonstrate that amyloid-induced cell death can involve multiple molecular mechanisms.…”
Section: ■ Discussionmentioning
confidence: 98%
“…Lipids are a large class of biological molecules that perform a large number of physiologically important functions in cells. Lipids are the major components of plasma and organelle membranes that determine membrane fluidity and permeability for molecules and ions. Lipids also act as secondary messengers in signal transduction across the plasma membrane . It was recently reported that amyloid proteins can interact with lipids forming complexes that have enhanced hydrophobicity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in a good agreement with the findings of Matveyenka et al . [61,76–80] which demonstrated that toxicity of insulin and lysozyme aggregates could be uniquely altered by lipids. Specifically, it was found that presence of PC at 1 : 1 molar ratios with insulin and lysozyme resulted in formation of small oligomers that exerted nearly three times lower cell toxicity compared to proteins fibrils grown in the lipid‐free environment [76–78].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the equimolar presence of fully saturated PS enabled the strongest enhancement of the rate of insulin aggregation compared to PS with unsaturated fatty acids. It was also found that insulin and lysozyme aggregates formed in the presence of PS exerted significantly different cell toxicities compared to the fibrils grown in the lipid-free environment. ,, Although the above-discussed findings can be valuable for the understanding of the role of PS in amyloidosis, they were obtained upon exposition of both insulin and lysozyme to the large unilamellar vesicles (LUVs) composed of PS alone. ,, The question to ask is whether an increase in the concentration of PS relative to zwitterionic lipids, such as PC and phosphatidylethanolamine (PE), primary constituents of the plasma membranes of most eucaryotic cells, would alter the rate of protein aggregation, as was evident for PS itself. To answer this question, we used a set of biophysical and molecular biology techniques that allowed for the determination of the rate of protein aggregation, the elucidation of morphology, secondary structure, and the toxicity of protein aggregates grown in the presence of lipid mixtures and in the lipid-free environment.…”
Section: Introductionmentioning
confidence: 99%